Indium tin oxide surface smoothing by gas cluster ion beam - Song, JH; Choi, DK; Choi, WK (ELSEVIER SCIENCE BV, 2002)
CO2 cluster ions are irradiated at the acceleration voltage of 25 kV to remove hillocks on indium tin oxide (ITO) surfaces and thus to attain highly smooth surfaces. CO2 monomer ions are also bombarded on the ITO surfaces at the same acceleration voltage to compare sputtering phenomena. From the atomic force microscope results, the irradiation of monomer ions makes the hillocks sharper and the surfaces rougher from 1.31 to 1.6 nm in roughness. On the other hand, the irradiation of CO2 cluster ions reduces the height of hillocks and planarize the ITO surfaces as smooth as 0.92 nm in roughness. This discrepancy could be explained by large lateral sputtering yield of the cluster ions and re-deposition of sputtered particles by the impact of the cluster ions on surfaces. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: FILMS